Investigation on sleeve joint purlin systems - Li, Yong (2009)
This thesis presents the experimental studies of the behaviour of sleeve joint purlin systems made of cold-formed steel Zed sections. Experimental tests on a variety of cleat-purlin and sleeve-purlin connections suitable for Zed section purlin systems have been conducted. A parametric study is carried out to determine the effect of various geometric and force related variables on the optimum design of Zed section purlin systems. Sufficient cases are then analyzed and tested, with the variation of the variables, such as purlin size, purlin thickness, sleeve size and thickness, sleeve length, bolt position, etc. within practical ranges n industry. The results of the tests were eventually used to develop a set of empirical expressions characterizing the general behaviour of connections on Zed section purlin systems.